AN EVALUATION OF THE IMPLEMENTATION OF EARLY CHILDHOOD EDUCATION 2013 CURRICULUM - Anggraeni ANGGRAENI (Journal of Education and Leadership in Education, 2021)
This study aims to evaluate the implementation of the 2013 PAUD curriculum related to planning, organizing, and implementation. The research was conducted at TKIT Nurul Izzah, located in Depok, West Java, using a discrepancy evaluation model consisting of six steps. Data collection was carried out by observation, structured interviews, and documentation. The results showed that 1) in terms of planning, the discrepancy was that there was no explanation regarding the curriculum used and the modifications made to the curriculum in the guidelines for the preparation of the curriculum at the educational unit level; 2). In terms of organizing, the discrepancy was that including the allocation of time / study load used exceeds the specified minimum standard, namely 1350 minutes per week; and 3) in terms of implementation, the discrepancy was that only the school committee know the vision, mission and objectives of education. However, semester, weekly, and daily planning has followed the regulation of the minister of education and culture Number 146 of 2014, documentation has also been included in the curriculum document, the learning methods have varied, the assessment techniques and instruments have followed the rules, and the learning outcomes report has a description and follow the existing rules. Thus, it can be concluded that the implementation of the 2013 early childhood educationcurriculum has gone quite well with the need for improvement in several parts, especially in the planning section.